Utilising Synthetic Biology to Produce Renewable Energy from Indonesiaâs Biodiversity: Inspiration from iGEM Competition - Kemal, Rahmat Azhari; Rini, Ika Agus; Oktaviani, Indah (Proceeding International Conference on Global Resource Conservation, 2015)
The emerging field of synthetic biology focuses on engineering biomolecular systems and cellular capabilities. It can be applied to a wide variety of applications, one of them is renewable energy production. Teams competing in the International Genetically Engineered Machine (iGEM) competition design and assemble biological devices able to do certain purposes such as producing renewable energy. Their ideas can be adapted by using compatible organisms available from Indonesiaâs rich biodiversity. Several ideas are highlighted in this review. One of them is the idea of recycling methanol in glycogen that can be used as carbon source for biofuel production. Methanol dehydrogenase from Indonesiaâs methylotrophic bacteria can substitute Bacillus methanolycus used in the system. The adapted ideas can serve as starting points for research, production, and implementation of renewable energy in Indonesia.Keywords: Biodiversity; iGEM; Indonesia; renewable energy; synthetic biology